Perancangan Dan Pembuatan Kondenser Untuk Sistem Refrigerasi Pada Pengering Beku Vakum Bengkuang Berkapasitas Maksimum 5 Kg - Paulus, Hendri; Martin, Awaludin (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Vacuum freeze drying is the latest technology in agricultural products that carry out the drying process, the vacuum freeze drying (VFD) method is a method that maintains color, aroma and taste. Freeze vacuum drying research by utilizing the exhaust heat of the condenser aims to optimize vacuum freeze drying so that the vacuum freeze drying process. The drying process with this method can reduce the energy consumption used by utilizing the condenser exhaust heat to accelerate the sublimation process of the water contained in the yam. In this research, a condenser has been successfully designed and made with an outer diameter of 0.0127 m and an inside diameter of 0.0102 m and a pipe length of 30.8 m.Keywords: vacuum freeze-drying, condenser, refrigeration system